Respostas

A melhor resposta!
  • Usuário do Brainly
2014-08-15T20:11:25-03:00
De acordo com a figura:

A=k^2-2k+3, B=-k^2+3k-1

C=2k-5 e D=k+4

a) Assim,

A+B+C=(k^2-2k+3)+(-k^2+3k-1)+(2k-5)

A+B+C=k^2-k^2-2k+3k+2k+3-1-5

A+B+C=3k-3=3(k-1)


b) B-C-D=(-k^2+3k-1)-(2k-5)-(k+4)

B-C-D=-k^2+3k-1-2k+5-k-4

B-C-D=-k^2+(3k-2k-k)+(5-1-4)

B-C-D=-k^2


c) C\cdot A=(2k-5)(k^2-2k+3)

C\cdot A=2k^3-4k^2+6k-5k^2+10k-15

C\cdot A=2k^3-9k^2+16k-15


d) D\cdot C=(k+4)(2k-5)

D\cdot C=2k^2-5k+8k-20

D\cdot C=2k^2+3k-20


e) C^2=(2k-5)^2

C^2=(2k)^2-2\cdot2k\cdot5+5^2

C^2=4k^2-20k+25


f) D^3=(k+4)^3

D^3=k^3+3k^2\cdot4+3k\cdot4^2+4^3

D^3=k^3+12k^2+48k+64
1 5 1
não é K não, o meu x que é assim.kkkkkk vou substituir K por x vale,,,,
2014-08-15T20:14:31-03:00
A) ( x^{2} -2x+3) + ( -x^{2} + 3x -1) + (2x - 5)
     x^{2} -2x + 3 - x^{2}  +3x - 1 + 2x -5
    3x - 3

b) (- x^{2} +3x -1) - (2x - 5) - (x + 4)
    - x^{2} +3x-1-2x+5-x-4
    - x^{2}

c) (2x - 5) ( x^{2} -2x +3)
    2 x^{3} - 4 x^{2} +6x - 5 x^{2} +10x -15
    2 x^{3} -9 x^{2} +16x - 15

d) (x + 4) (2x - 5)
    2 x^{2} -5x+8x - 20
    2 x^{2} + 3x - 20

e) (2x-5) ^{2}
    4 x^{2} -20x + 25

f) (x+4) ^{3}
   (x+4) ^{2} (x+4)
   ( x^{2} +8x+16) (x+4)
    x^{3}+4 x^{2} +8 x^{2} +32x+16x+64
    x^{3} +12 x^{2} +48x+64
2 3 2